2015
DOI: 10.1007/s00520-015-2874-7
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of Kinesio® Taping in patients with arm lymphedema: medical device clinical study

Abstract: Kinesio Tex Gold bandage by the KT technique proved to be safe and tolerable in patients with lymphedema, with improved functionality and no change of the affected limb volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 15 publications
0
26
0
3
Order By: Relevance
“…50 54 Other noticeable findings in the literature were that kinesiology taping could be an alternate choice for patients who are unsuitable for decongestive lymphoedema therapy, 48 51 and could be used for 'challenging areas' of the body, although there was concern about hygiene associated with the tape in situ. 49 A clinical study (n=24), 54 found that kinesiology taping was not associated with reductions in lymph volume in patients with breast cancer; however, it was reported by the patients that they felt more confident when performing daily activities and this resulted in improvements of upper limb functionality. A patient in that study reported peeling of the skin and redness.…”
Section: Discussionmentioning
confidence: 99%
“…50 54 Other noticeable findings in the literature were that kinesiology taping could be an alternate choice for patients who are unsuitable for decongestive lymphoedema therapy, 48 51 and could be used for 'challenging areas' of the body, although there was concern about hygiene associated with the tape in situ. 49 A clinical study (n=24), 54 found that kinesiology taping was not associated with reductions in lymph volume in patients with breast cancer; however, it was reported by the patients that they felt more confident when performing daily activities and this resulted in improvements of upper limb functionality. A patient in that study reported peeling of the skin and redness.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports and studies without a comparison group suggest that kinesiology taping is beneficial or is as effective as conventional treatments for reducing lymphoedema (eg, compression sleeves) in cancer 19–27. These reports also suggest that kinesiology taping may be beneficial for mitigating associated symptoms in the lymphoedema limb including pain,20 muscle tension,19 feeling of fullness/tightness/heaviness,20 22 and improving joint ROM19 and tissue texture,21 with overall improvements in disability22 and activities of daily living 27. Kinesiology tape is comfortable to wear compared with compression garments and may be an alternative option for patients with poor short-stretch bandage compliance or to those that are contraindicated to decongestive compression therapy 20 21 23 24 27…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have demonstrated that Kinesio taping is an ineff ective method for limb volume reduction in patients with lymphoedema [71,72].…”
Section: Kinesio Tapingmentioning
confidence: 99%